Analisis Return On Assets, Return On Equity, Net Profit Margin dan Gross Profit Margin untuk Mengukur Kinerja Keuangan PT Unilever Indonesia Tbk - Aintana Khilya Fuadhina; Riska Agustin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk for the 2022–2024 period, focusing on key profitability ratios: Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Gross Profit Margin (GPM). The method used is a descriptive quantitative approach, with data obtained from the company’s annual financial reports. The results show that overall, the company’s profitability remained in the good category during the analyzed period. However, there are indications of a decline in asset efficiency, reflected in the declining ROA ratio and a decline in net profit margin, reflected in the NPM. Nevertheless, the ROE and GPM ratios continue to show positive performance. These findings illustrate the importance of management in maintaining asset efficiency and increasing net profit margins. Therefore, management and investors are expected to use the results of this study to formulate better financial strategies to maintain and improve the company’s profitability in the long term.